Graphene encapsulated non-precious metal hydrogen evolution electrocatalyst and preparation method and application thereof

Through graphene encapsulation and Ti-doped NiMo catalyst, the problem of difficulty in catalyzing HER reactions in an acidic environment is solved, high activity and acid resistance are achieved, and low-priced, suitable for large-scale applications.

CN115747864BInactive Publication Date: 2025-02-11HARBIN INST OF TECH SHENZHEN GRADUATE SCHOOL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211277489.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively catalyze HER reactions in acidic environments, and precious metal catalysts are expensive, which limits their large-scale application.

Method used

Inexpensive nickel-molybdenum alloy (NiMo) is encapsulated by graphene, and through Ti doping and graphene packaging steps, the electron transfer capacity between the NiMo/graphene interface is enhanced, the electron density on the surface of graphene is improved, thereby enhancing the electrocatalytic activity of HER.

Benefits of technology

It has achieved excellent hydrogen evolution catalytic activity and acid resistance in an acidic environment, and is cheap, and overcomes the problem of high cost of precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115747864B_ABST
    Figure CN115747864B_ABST
Patent Text Reader

Abstract

The present invention provides a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst and a preparation method and application thereof. The preparation method comprises: step S1, preparing Ti-doped NiMoO 4 , wherein the mass percentage of Ti doping is 0.1-5%; step S2, Ti-doped NiMoO 4 In an inert gas / hydrogen mixed atmosphere, calcining at 800-850°C for 1-60 min to obtain a NiMo alloy; step S3, cooling to 700-750°C, introducing pyridine vapor for 1s-2min, and growing a graphene encapsulation layer; stopping heating, and after the temperature drops to room temperature, obtaining a graphene-encapsulated Ti-doped NiMo alloy material. The catalyst of the technical solution of the present invention has excellent hydrogen evolution catalytic activity, and improves the ability to resist acid corrosion, enables non-precious metals to catalyze HER reactions in an acidic environment, has better catalytic stability, and is cheap.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material technology, and in particular relates to a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane water electrolysis technology is a highly promising green hydrogen production method. However, the acidic environment inside the electrolyzer limits the selection of HER catalysts to a few Pt-based precious metals. However, the high price of Pt-based precious metals limits their large-scale application. Therefore, developing acid-resistant non-precious metal HER catalysts to replace Pt precious metals to catalyze HER reactions in acidic environments is one of the important research directions of current proton exchange membrane water electrolysis technology.

[0003] Graphene has excellent chemical stability, so using graphene to encapsulate non-precious metals can effectively prevent acid corrosion and is an effective means of preparing acid-resistant catalysts. Graphene encapsulation can significantly improve the catalytic stability of non-precious metals in acidic environments, but graphene will also hinder the contact between reactants and catalytic active sites on the metal surface, resulting in reduced catalyst performance. Therefore, how to improve the HER activity of graphene-encapsulated non-precious metal catalysts is the key. Summary of the invention

[0004] In view of the above technical problems, the present invention discloses a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst and a preparation method and application thereof, which has excellent hydrogen evolution catalytic activity and better catalytic stability.

[0005] To this end, the technical solution adopted by the present invention is:

[0006] A method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst comprises the following steps:

[0007] Step S1, preparing Ti-doped NiMoO4, wherein the mass percentage of Ti doping is 0.1-5%;

[0008] Step S2, calcining Ti-doped NiMoO4 in an inert gas / hydrogen mixed atmosphere at 800-850° C. for 1-60 min to obtain a NiMo alloy; the inert gas is preferably argon, helium or neon;

[0009] Step S3, cooling to 700-750°C, introducing pyridine vapor for 1s-2min to grow a graphene encapsulation layer; stopping heating, and after the temperature drops to room temperature, obtaining a graphene-encapsulated Ti-doped NiMo alloy material (G / Ti-NiMo).

[0010] Using this technical solution, a non-precious metal HER catalyst with high activity and acid resistance is prepared using cheap nickel-molybdenum alloy (NiMo) as a template through titanium (Ti) doping and graphene encapsulation steps. This catalyst is based on the regulation of electron transfer between the graphene / metal interface, which enhances the electron density on the graphene surface, thereby improving the HER electrocatalytic activity of the material. It has both acid resistance and high activity, and is inexpensive.

[0011] As a further improvement of the present invention, step S1 includes: preparing a Ni source solution, adding a Mo source material, and after dissolving, adding a Ti source solution to obtain a mixed solution, keeping the mixed solution in an autoclave at 150-170° C. for 6-12 h, washing and drying, and obtaining Ti-doped NiMoO4 powder. Further, the mixed solution is kept at 160° C. for more than 6 h, and after washing and drying, Ti-doped NiMoO4 powder is obtained.

[0012] As a further improvement of the present invention, the Ni source is NiCl2, the Mo source is Na2MoO4, the Ti source is TiCl3, and the molar ratio of the Ni source to the Mo source is 0.8~1.2:1.

[0013] As a further improvement of the present invention, in step S2, the calcination time is 10 to 60 minutes. Further, in step S2, the calcination time is 10 to 30 minutes. Further, the calcination time is 20 minutes.

[0014] As a further improvement of the present invention, the mass percentage of the Ti doping is 0.1-1%. Further, the mass percentage of the Ti doping is 0.1-0.5%. More preferably, the mass percentage of the Ti doping is 0.5%.

[0015] As a further improvement of the present invention, the graphene-encapsulated Ti-doped NiMo alloy material obtained in step S3 has an area ratio of 2D peak to G peak in the Raman spectrum of 1-2.

[0016] As a further improvement of the present invention, in step S3, the time for passing the pyridine vapor is 3 to 60 seconds. Further, the time for passing the pyridine vapor is 5 to 30 seconds. Further preferably, the time for passing the pyridine vapor is 10 seconds.

[0017] The present invention also discloses a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst, which is prepared by using the preparation method of the graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst as described in any one of the above items.

[0018] The present invention also discloses the use of the graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst as described above, which is used in hydrogen production by proton exchange membrane water electrolysis.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] First, the graphene-encapsulated Ti-doped NiMo alloy hydrogen evolution catalytic material of the technical solution of the present invention effectively enhances the electron transfer ability between the NiMo / graphene interface through Ti doping, increases the electron density on the graphene surface, and further promotes HER activity, and has excellent hydrogen evolution catalytic activity.

[0021] Second, the catalyst of the technical solution of the present invention improves the ability of NiMo to resist acid corrosion through graphene encapsulation, allowing non-precious metals to catalyze HER reactions in acidic environments, and exhibits catalytic stability in acidic electrolytes that is much higher than that of commercial Pt / C catalysts.

[0022] Thirdly, the catalyst of the technical solution of the present invention is cheap, which overcomes the disadvantage of the high price of the current commercial Pt / C catalyst and has a significant price advantage. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM photograph of the catalyst obtained in Example 1 of the present invention.

[0024] Figure 2 This is the XRD pattern of the catalyst obtained in Example 1 of the present invention.

[0025] Figure 3 It is a comparative XPS Ti 2p spectrum of the catalysts G / Ti-NiMo and G / NiMo in Example 1 of the present invention.

[0026] Figure 4 1 is a comparative Raman spectrum of catalyst G / Ti-NiMo and Ti-NiMo in Example 1 of the present invention.

[0027] Figure 5 The HER performance of the catalyst G / Ti-NiMo of Example 1 of the present invention is compared with that of G / NiMo and a commercial Pt / C catalyst in 0.5 mol / LH2SO4.

[0028] Figure 6 The catalytic stability test results of the catalyst G / Ti-NiMo of Example 1 of the present invention and the commercial Pt / C catalyst in 0.5 mol / L H2SO4 are shown.

[0029] Figure 7 It is a comparison curve of HER catalytic polarization of catalyst samples with different Ti doping amounts in the embodiment of the present invention.

[0030] Figure 8 It is a comparison diagram of Raman spectra of catalyst samples obtained with different pyridine vapor introduction times in the embodiments of the present invention.

[0031] Fig. 9 HER catalytic polarization curves of catalyst samples obtained with different pyridine vapor introduction times in the embodiments of the present invention. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described in further detail below.

[0033] The graphene encapsulated non-precious metal hydrogen evolution electrocatalyst, the specific preparation steps include:

[0034] Step 1: Dissolve NiCl2·2H2O in pure water, slowly add Na2MoO4·2H2O under strong stirring, and after complete dissolution, drop an appropriate amount of TiCl3 solution, and then transfer to a polytetrafluoroethylene-lined autoclave, and obtain Ti-doped NiMoO4 powder (Ti-NiMoO4) after heat preservation, washing, and drying. The heat preservation temperature is 160 ℃, and the heat preservation time is 6~12 h.

[0035] Step 2: Place the obtained Ti-NiMoO4 powder in a tube furnace and calcine it in an argon / hydrogen mixed atmosphere to reduce NiMoO4 to NiMo alloy; wherein the calcination temperature is 800-850°C and the calcination holding time is 1-60 min. Furthermore, the calcination holding time is 10-30 min.

[0036] Step 3: Pass pyridine vapor into a tube furnace to grow a graphene encapsulation layer; wherein the temperature of the tube furnace is 700-750° C., and the time for passing pyridine vapor is 1 s to 2 min. Preferably, the time for passing pyridine vapor is 5 s to 30 s.

[0037] Step 4: Stop heating, wait until the temperature drops to room temperature, take out the sample, and obtain a graphene-encapsulated Ti-doped NiMo alloy material (G / Ti-NiMo).

[0038] Preferably, in step 1, the amount of NiCl2·2H2O is 0.3~0.8 g, the amount of Na2MoO4·2H2O is 0.3~0.8 g, the amount of TiCl3 solution is 1~400 μL, and the mixture is kept at 160 ºC for 6~12 h.

[0039] The following describes it in conjunction with specific embodiments.

[0040] Example 1

[0041] The graphene encapsulated non-precious metal hydrogen evolution electrocatalyst is prepared by the following steps:

[0042] (1) Weigh 0.3 g NiCl2·2H2O and dissolve it in pure water. Then slowly add 0.3 g Na2MoO4·2H2O under vigorous stirring. Then drop 9.25 μL of TiCl3 solution. After vigorous stirring for 20 min, transfer the solution to an autoclave with a polytetrafluoroethylene liner and place it in a muffle furnace at 160 ºC for 10 h. After washing and drying, Ti-doped NiMoO4 powder (Ti-NiMoO4) was obtained.

[0043] (2) Ti-NiMoO4 powder was placed in a tube furnace and calcined at 800 ºC for 30 min in an argon / hydrogen mixed atmosphere.

[0044] (3) The temperature of the tube furnace was lowered to 700 °C and pyridine vapor was introduced into the tube furnace for 5 s.

[0045] (4) Stop heating, wait until the temperature drops to room temperature, take out the sample, and obtain a graphene-encapsulated Ti-doped NiMo alloy material (G / Ti-NiMo), wherein the doping amount of Ti is 0.5%, referred to as G / 0.5Ti-NiMo.

[0046] The scanning electron microscope (SEM) photograph of the G / Ti-NiMo material obtained in Example 1 is as follows Figure 1 As shown in Figure 1, the sample is a nanowire structure with a diameter of about 100 nm. The X-ray diffraction (XRD) pattern of the G / Ti-NiMo material is shown in Figure 1. Figure 2 As shown, the spectral peaks match well with the NiMo standard cards (PDF #48-1745) and Ni4Mo (PDF #65-5480), proving that the prepared material is a NiMo alloy. It is worth noting that the peak position of the graphene-encapsulated undoped NiMo alloy (G / NiMo) at 43.8° is the NiMo (133) crystal plane, but the peak position of the NiMo (133) crystal plane in G / Ti-NiMo is 43.6°, indicating that Ti doping changes the interplanar spacing of the NiMo alloy. Comparison of G / Ti-NiMo and G / NiMo (graphene-encapsulated NiMo alloy, no Ti doping) X-ray photoelectron spectroscopy (XPS) high-resolution Ti 2p spectrum is shown in Figure 3 As shown, it is proved that the G / Ti-NiMo sample contains Ti element, while G / NiMo does not. The Raman spectra of the G / Ti-NiMo sample and Ti-NiMo (Ti-doped NiMo alloy without encapsulated graphene) are shown in Figure 2. Figure 4 As shown, the Raman spectrum of the G / Ti-NiMo sample shows the characteristic spectrum of graphene, while the Ti-NiMo sample without graphene encapsulation has no corresponding spectrum, proving that graphene is encapsulated on the surface of NiMo alloy.

[0047] In Ar-saturated 0.5 mol / L H2SO4 electrolyte, the carbon cloth modified with G / Ti-NiMo material was used as the working electrode, the graphite rod was used as the counter electrode, and the Ag / AgCl with salt bridge was used as the reference electrode. Linear sweep voltammetry (LSV) test and chronoamperometry (CA) catalytic stability test were carried out under three-electrode system conditions. The HER polarization curves of G / Ti-NiMo, G / NiMo and commercial 20 wt.% Pt / C are shown in Figure 2. Figure 5 As shown in the figure, the results show that Ti doping significantly improves the catalytic performance of graphene encapsulated NiMo, which is close to the performance of Pt-based catalysts. The catalytic stability test results are shown in the figure. Figure 6 As shown in the figure, it can be seen that after 120 hours of continuous testing in an acidic environment, the catalytic performance of G / Ti-NiMo has almost no attenuation, while the performance of commercial 20 wt.% Pt / C decreases by 60%, indicating that compared with the 20 wt.% Pt / C in the prior art, G / Ti-NiMo has a better ability to resist acid corrosion and has better catalytic stability.

[0048] Example 2

[0049] Based on Example 1, the difference of this example is that in step (1), the volumes of the TiCl3 solution added are 1.85 µL, 18.5 µL, 92.5 µL, and 370 µL, respectively, and the rest is the same as step (1), and Ti-NiMoO4 with Ti doping amounts of 0.1%, 1%, 5%, and 20% are obtained, respectively. The sample names are 0.1Ti-NiMoO4, 0.5Ti-NiMoO4, 1.0Ti-NiMoO4, 5.0Ti-NiMoO4, and 20.0Ti-NiMoO4, respectively.

[0050] The other steps are the same as in Example 1.

[0051] The obtained graphene-encapsulated Ti-doped NiMo alloy materials are G / 0.1Ti-NiMo, G / 1.0Ti-NiMo, G / 5.0Ti-NiMo, and G / 20.0Ti-NiMo, respectively.

[0052] A graphene-encapsulated NiMo was prepared as a comparison, that is, no TiCl3 solution was added in step (1), and the rest was the same as in Example 1, referred to as G / NiMo.

[0053] The performance of G / 0.5Ti-NiMo obtained in Example 1 was compared with that of G / NiMo, 0.1Ti-NiMoO4, 0.5Ti-NiMoO4, 1.0Ti-NiMoO4, 5.0Ti-NiMoO4 and 20.0Ti-NiMoO4 obtained in this example.

[0054] In an Ar-saturated 0.5 mol / L H2SO4 solution, G / Ti-NiMo samples with different Ti doping amounts were loaded on carbon cloth as the working electrode, graphite rod as the counter electrode, and double salt bridge Ag / AgCl as the reference electrode. Linear sweep voltammetry (LSV) was performed under three-electrode system conditions at a sweep rate of 5 mV / s. The test results are shown in Figure 2. Figure 7 As shown, it can be seen that the current density of G / NiMo, G / 0.1Ti-NiMo, G / 0.5Ti-NiMo, G / 1.0Ti-NiMo, G / 5.0Ti-NiMo, and G / 20.0Ti-NiMo samples reached 40 mA / cm 2 , the required overpotentials are 119, 107, 101, 129, 137, and 177 mV, respectively. It is worth noting that the HER performance of G / 0.1Ti-NiMo and G / 0.5Ti-NiMo samples exceeds that of the non-Ti-doped sample G / NiMo, among which the G / 0.5Ti-NiMo sample has the best catalytic performance.

[0055] Example 3

[0056] Based on Example 1, the difference of this example is that in step (3), the time of introducing pyridine vapor is different, 30 seconds and 2 minutes respectively as two samples, and the other steps are the same as Example 1.

[0057] The performance of the samples obtained by introducing pyridine vapor for 30 seconds and 2 minutes was compared with that of the sample in Example 1. Figure 8 This is a comparison of the Raman spectra of samples with different pyridine vapor introduction times. Fig. 9 is the HER catalytic polarization curve of the samples with different pyridine vapor introduction time. The area ratio of the 2D peak to the G peak in the Raman spectrum ( I 2D / I G ) can reflect the number of graphene encapsulation layers, I 2D / I G The lower the value, the more graphene layers there are. Figure 2 It can be clearly seen that as the pyridine vapor introduction time increases, the number of graphene layers increases accordingly. Figure 3 The relationship between the HER performance of graphene-encapsulated catalysts and the number of graphene layers is demonstrated, indicating that an increase in the number of layers will lead to a decrease in catalytic activity.

[0058] It can be seen from the above experimental data that the technical solution of the present invention effectively promotes HER activity through Ti doping, has excellent hydrogen evolution catalytic activity, and has better acid environment resistance stability and low price compared to existing commercial Pt / C catalysts.

[0059] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst, characterized in that: The steps include: Step S1, preparing Ti-doped NiMoO4, wherein the mass percentage of Ti doping is 0.1-5%; Step S1 comprises: preparing a Ni source solution, adding a Mo source material, and after dissolving, adding a Ti source solution to obtain a mixed solution, keeping the mixed solution in an autoclave at 150-170° C. for 6-12 h, washing and drying, and obtaining Ti-doped NiMoO4 powder; the Ni source is NiCl2, the Mo source is Na2MoO4, the Ti source is TiCl3, and the molar ratio of the Ni source to the Mo source is 0.8-1.2:1; Step S2, calcining Ti-doped NiMoO4 in an inert gas / hydrogen mixed atmosphere at 800-850° C. for 1-60 min to obtain a NiMo alloy; Step S3, cooling to 700-750°C, introducing pyridine vapor for 1s-2min to grow a graphene encapsulation layer; stopping heating, and after the temperature drops to room temperature, obtaining a graphene-encapsulated Ti-doped NiMo alloy material.

2. The method for preparing the graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst according to claim 1, characterized in that: In step S2, the calcination time is 10 to 30 minutes.

3. The method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst according to claim 2, characterized in that: The mass percentage of the Ti doping is 0.1-0.5%.

4. The method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst according to claim 1, characterized in that: The inert gas is argon, helium or neon.

5. The method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst according to claim 1, characterized in that: The graphene-encapsulated Ti-doped NiMo alloy material obtained in step S3 has an area ratio of 2D peak to G peak in the Raman spectrum of 1-2.

6. The method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst according to claim 1, characterized in that: In step S3, the pyridine vapor is introduced for 5 to 30 seconds.

7. Graphene encapsulated non-precious metal hydrogen evolution electrocatalyst, characterized in that: The catalyst is prepared by the method for preparing a graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst as claimed in any one of claims 1 to 6.

8. The use of the graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst as claimed in claim 7, characterized in that: The graphene-encapsulated non-precious metal hydrogen evolution electrocatalyst is used in hydrogen production by proton exchange membrane water electrolysis.

Citation Information

Patent Citations

  • Difunctional Pd / Ni-Mo / C composite catalyst and preparation method thereof

    CN105990588A

  • RuNi alloy nano composite material as well as preparation method and application thereof

    CN113275562A